Morphological aspects of the liver of the Podocnemis expansa (Testudines, podocnemididae) - Moura, L. R.; Santos, A. L Q; Beletti, M. E.; Vieira, L. G.; Orpinelli, S. R.; Alves Júnior, J. R. [UNESP] (My University, 2012)
The liver of P. expansa was characterized morphohistologically. To this end, twenty livers from clinically healthy male and female Podocnemis expansa, weighing from 2.0 to 4,5 kg, supplied by the commercial breeder Fazenda Moenda da Serra, in Araguapaz, state of Goiás, Brazil, were analyzed macro-and microscopically. The coelomatic cavity was opened and the topography of the fresh organs was examined visually. After the histological preparation, the slides were stained with Hematoxylin and Eosin (HE), Periodic Acid-Schiff (PAS), Gomori Trichrome, Reticulin and Picrosirius. The liver of P. expansa is a voluminous organ with an approximately rectangular shape and brown coloration, varying from light to dark shades, and is divided into a right lobe, left lobe, and a central portion. The right lobe is the largest of the three portions. The gall bladder is located in a depression in the caudal portion of the right lobe, where the gall duct begins and empties into the duodenum. Histologically, the hepatocytes are arranged in the form of double cords surrounded by winding sinusoidal capillaries. In cross section, they resemble acini containing approximately two to five hepatocytes surrounding a probable central biliary canaliculus. The hepatocytes are polyhedral or pyramidal in shape, of uniform size, with a few central nuclei and others displaced peripherally, and the cytoplasm is little eosinophilic when analyzed by the HE staining technique. The parenchyma is supported by delicate reticular fibers surrounding hepatocytes and sinusoids. The parenchyma and perisinusoidal spaces contain large quantities of melanomacrophages, mainly close to the portal spaces.
Keywords: Histology; Liver; Morphology; Podocnemididae; Reptiles